(untitled) (ACTA MEDICA PERUANA, 2024)
BY-PASS is one of the procedures from wicb vascular surgery has greatly beneficed. This operation was first performed by the French surgeon Jean Kunlin, an assistant of Rene Leriche. The first three cases of patients on wbow Kunlin performed a venous by-pass are presented based on the surgeon’s personal comunication to the authors.